Makna Penggunaan Repetisi Frase “TUHAN Menyesal” dalam Yeremia 26:1-24 - Josua, Rezky Alfero; Sualang, Farel Yosua; Sulistya, Philipus Pada (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
The purpose of this article is to show that in Jeremiah 26 there is a ladder repetition of the phrase